Analysis of the thermostable direct hemolysin (tdh) gene and the tdh-related hemolysin (trh) genes in urease-positive strains of Vibrio parahaemolyticus isolated on the West Coast of the United States. - Okuda, J (1997)
Urease-positive (Ure+) and urease-negative (Ure-) strains of Vibrio parahaemolyticus isolated from patients on the West Coast of the United States between 1979 and 1995 were analyzed for the thermostable direct hemolysin (tdh) gene and the tdh-related hemolysin (trh) genes (trh1 and trh2). The DNA colony hybridization method with the polynucleotide probes was used to determine the distribution of the genes. Of 60 Ure+ strains, 59 strains (98%) had the trh (either trh1 or trh2) gene and 54 strains (90%) carried the tdh gene. The absence of the trh gene or a related sequence in an exceptional Ure+ strain was confirmed by Southern blot analyses. The stronger correlation with the trh gene than with the tdh gene was mostly attributable to strains possessing only the trh2 gene. Of 25 Ure- strains, 20 strains (80%) had the tdh gene but none had the trh gene. These results indicate a very strong correlation between the Ure+ phenotype and the trh gene and are consistent with those reported for strains isolated in Asia. The Ure+ strains carrying the trh genes were not restricted to a unique group of the strains. The O4:K12 strains carrying the trh1 gene have predominantly been isolated since 1979. However, strains of various non-O4:K12 serovars carrying either the trh1 or the trh2 gene became predominant after 1992. In addition, analysis by the arbitrarily primed PCR method revealed two subgroups within the selected Ure+ O4:K12 strains. Hybridization tests with oligonucleotide probes demonstrated that the trh1 sequences of the West Coast strains differ to some extent from those of Asian strains. Nevertheless, a PCR method previously established to detect both the trh1 and the trh2 genes in Asian strains could detect 98% of those genes in the West Coast strains.